EFFECT OF DATE FRUIT (PHOENIX DACTYLIFERA L.) EXTRACT ON TNFα LEVELS AND BRAIN WEIGHT OF ALZHEIMER’S MODEL RATS - Marintan, Elita; Wasita, Brian; Magna, Adi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Background: Alzheimer's disease (AD) is aÂ neurodegenerative disorder marked by brain inflammation resulted in structural damage and brain dysfunction. Tumor necrosis factor Î± (TNFÎ±) is a cytokine that plays an important role in inflammation. Dates fruit may help to fight oxidative stress and inflammation in the brain.Objective: To determine the effect of date fruit extracts on blood TNFÎ± levels and brain weight of alzheimerâ€™s model rats.Methods: This research is a laboratory experimental study by post-test only with control group design using alzheimer model rats. This study used 6 treatment groups with simple randomization. Each treatment group was represented by 8 Sprague Dawley rats. The normal control group (KN) was not induced by Hcy and was not given date palm extract, the negative control group (K-) was the Alzheimer's experimental rats which was not given the date palm extract, the positive group was the Alzheimer's experimental rats which was given the Donepezil (K+). Groups P1, P2, P3 were Alzheimer's experimental rats that were given date palm extract at a dose of 200, 400,800 mg / kgBW / day. The effect of date palm extract dosage on TNFÎ± levels and brain weight were analyzed using the One Way Anova test followed by Tukey's post hoc test.Results: The difference in TNFÎ± levels between groups showed a significant difference (p = 0.00). Meanwhile there was no significant difference in brain weight among all groups (p > 0,05).Â Conclusion: Date palm extract at doses of 200, 400, 800 mg / kgBW can decrease blood TNFÎ± levels of Alzheimerâ€™s model rats.